The multifaceted determinants of Saudi foreign policy in the gulf: Interplay of domestic, ideational, and systemic factors - Waleed. F AlFaisal; Aimi anuar (Environment and Social Psychology, 2025)
Background: Saudi Arabia’s foreign policy in the Gulf region (2011-2023) is driven by a complex interplay of interests, motivations, and regional dynamics. Existing scholarships often overlook the intricate interactions between these elements and lack a comprehensive theoretical framework synthesizing religious influence, regional standing, and dynamic leadership. Objective: This study aimed to address this gap by providing a more integrated and nuanced understanding of Saudi foreign policy. It sought to analyze the multi-faceted interactions among strategic security imperatives, economic motivations, geopolitical factors, religious influences, aspirations for regional leadership, and domestic political contexts. Methodologies: A mixed-methods approach was employed, integrating both qualitative and quantitative research methodologies. This involved semi-structured interviews with prominent policymakers and experts, subjected to thematic analysis, alongside the analysis of secondary economic, political, and security data within the Gulf. Neoclassical realism and constructivism served as theoretical frameworks, enabling a comprehensive exploration of both material and ideational factors influencing Saudi foreign policy. Results: The study revealed that Saudi foreign policy was fueled by aspirations for regional dominance, religious influence, and an urgent need for economic diversification. It shed light on how these internal motivations interacted with external regional dynamics, especially during the tumultuous era of 2011-2023, marked by the Arab Spring, the rise of ISIS, and increased tensions with Iran. Detailed case studies of interventions in Yemen, the Qatar crisis, and the establishment of relations with Israel elucidated the rationale behind key policy decisions. Challenges identified included domestic political constraints, economic diversification efforts, and ongoing regional instability. Conclusions: Saudi foreign policy is a complex and dynamic process shaped by the intricate interplay of internal drivers and external pressures. The study’s integrated analysis transcended simplistic narratives, offering a thorough and nuanced understanding of these determinants. Recommendations: To successfully navigate the Gulf region’s complex geopolitical landscape and secure its future, Saudi Arabia requires a sophisticated and proactive strategy. This approach should blend assertiveness with diplomacy, prioritize economic diversification, foster strategic partnerships, and ensure a cohesive integration of both domestic and foreign policy.